Interactions between Plant Metabolites Affect Herbivores: A Study with Pyrrolizidine Alkaloids and Chlorogenic Acid - Liu, Xiaojie; Vrieling, Klaas; Klinkhamer, Peter G.L. (Frontiers in Plant Science, 2017)
The high structural diversity of plant metabolites suggests that interactions among them should be common. We investigated the effects of single metabolites and combinations of plant metabolites on insect herbivores. In particular we studied the interacting effects of pyrrolizidine alkaloid (PAs), and chlorogenic acid (CGA), on a generalist herbivore, Frankliniella occidentalis. We studied both the predominantly occurring PA N-oxides and the less frequent PA free bases. We found antagonistic effects between CGA and PA free bases on thrips mortality. In contrast PA N-oxides showed synergistic interactions with CGA. PA free bases caused a higher thrips mortality than PA N-oxides while the reverse was through for PAs in combination with CGA. Our results provide an explanation for the predominate storage of PA N-oxides in plants. We propose that antagonistic interactions represent a constraint on the accumulation of plant metabolites, as we found here for Jacobaea vulgaris. The results show that the bioactivity of a given metabolite is not merely dependent upon the amount and chemical structure of that metabolite, but also on the co-occurrence metabolites in e.g. plant cells, tissues and organs. The significance of this study is beyond the concerns of the two specific groups tested here. The current study is one of the few studies so far that experimentally support the general conception that the interactions among plant metabolites are of great importance to plant-environment interactions.